2011
DOI: 10.1111/j.1600-079x.2011.00933.x
|View full text |Cite
|
Sign up to set email alerts
|

Melatonin prevents human pancreatic carcinoma cell PANC‐1‐induced human umbilical vein endothelial cell proliferation and migration by inhibiting vascular endothelial growth factor expression

Abstract: Melatonin is an important natural oncostatic agent, and our previous studies have found its inhibitory action on tumor angiogenesis, but the mechanism remains unclear. It is well known that vascular endothelial growth factor (VEGF) plays key roles in tumor angiogenesis and has become an important target for antitumor therapy. Pancreatic cancer is a representative of the most highly vascularized and angiogenic solid tumors, which responds poorly to chemotherapy and radiation. Thus, seeking new treatment strateg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
53
0
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 50 publications
(56 citation statements)
references
References 36 publications
2
53
0
1
Order By: Relevance
“…Cristofanon et al described that melatonin can induce NF-κB activation in U937 cells and suggested a possible involvement for ROS induced by melatonin (Cristofanon et al, 2009). In contrast to cancer cells, melatonin did not induce cytotoxicity in noncancer cells, including human umbilical vein endothelial cells (Cui et al, 2012), primary hepatocytes (Kojima et al, 1997), neuronal stem cells (Fu et al, 2011), and HT22, a mouse hippocampal cell line (Rodriguez et al, 2013). A further study reported that in human platelets, melatonin considerably increased the generation of intracellular ROS and Ca…”
Section: Prooxidant Actions Of Melatoninmentioning
confidence: 99%
“…Cristofanon et al described that melatonin can induce NF-κB activation in U937 cells and suggested a possible involvement for ROS induced by melatonin (Cristofanon et al, 2009). In contrast to cancer cells, melatonin did not induce cytotoxicity in noncancer cells, including human umbilical vein endothelial cells (Cui et al, 2012), primary hepatocytes (Kojima et al, 1997), neuronal stem cells (Fu et al, 2011), and HT22, a mouse hippocampal cell line (Rodriguez et al, 2013). A further study reported that in human platelets, melatonin considerably increased the generation of intracellular ROS and Ca…”
Section: Prooxidant Actions Of Melatoninmentioning
confidence: 99%
“…However, the mechanisms of melatonin's antiangiogenic in any tumor including NSCLC are still unclear. Numerous studies have documented that melatonin exhibits antiangiogenic actions, in part, by downregulating VEGF and HIF-1α in several cancers via different mechanisms; the cancer types included breast [16, 149], prostate [150152], colon [153, 154], liver [155], and pancreatic cancer [156, 157]. These studies may provide reference for the future work in the NSCLC research field.…”
Section: Potential Directionsmentioning
confidence: 99%
“…To assess the effect of melatonin on hypoxia-induced HUVEC migration, we treated cells with different doses of melatonin [8,20] and measured the migration rate by wound closure assay. As shown in Figure 1A, an upregulation of HUVEC migration occurred after exposure to hypoxia; the cell migratory ability decreased gradually with increasing doses of melatonin.…”
Section: Resultsmentioning
confidence: 99%
“…For the cell migration assay, the cell wound closure assay was performed as previously described [20]. Briefly, a scratch was made in the monolayer of HUVEC cells by using a 10-µL pipette tip.…”
Section: Methodsmentioning
confidence: 99%